2021
DOI: 10.1177/08445621211063702
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between new Nurses’ Gerontological Education, Personal Attitudes Toward Older Adults, and Intentions to Work in Gerontological Care Settings in Ontario, Canada

Abstract: Background The older adult population in Canada is increasing, and many will require care within an acute geriatric unit (AGU) or long-term care facility (LTCF). However, the nursing workforce is not growing at the same pace as the population is aging. New graduate nurses may be able to fill this gap; therefore, it is important to understand their intentions of working in gerontological care settings (i.e., AGU or LTCF). Aim To examine if nursing education and personal attitudes toward older adults influence n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As individuals grow older, their social participation and interaction may decrease, and they may depend more on material and spiritual support from others to relieve stress and enhance their physical and mental health. Research has demonstrated the signi cant impact of social interaction on the quality of life of older individuals, underscoring the crucial role of social activities in their overall well-being [40]. Engaging in social activities not only improves health from various perspectives but also results in lower mortality and higher survival rates among older adults [41].…”
Section: Discussionmentioning
confidence: 99%
“…As individuals grow older, their social participation and interaction may decrease, and they may depend more on material and spiritual support from others to relieve stress and enhance their physical and mental health. Research has demonstrated the signi cant impact of social interaction on the quality of life of older individuals, underscoring the crucial role of social activities in their overall well-being [40]. Engaging in social activities not only improves health from various perspectives but also results in lower mortality and higher survival rates among older adults [41].…”
Section: Discussionmentioning
confidence: 99%
“…Both data were compared to highlight similarities or inconsistencies in order to gain deeper insights and perspectives. Using different methods allows for triangulation or confirmation of findings (Creswell et al, 2003;Sauro, 2015).…”
Section: Methodsmentioning
confidence: 99%